Strategi Bisnis Hotel Syariah dalam Mencegah Perilaku Disosiatif: Studi di Hotel Family Syariah 2 Yogyakarta - Hurriyatul Alawiyah Hasan, Fanny Faizah; Fauzi, Yayan; Mulyawisdawati, Richa Angkita (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The hotel business often faces negative stigma due to public perception that associates it with deviant behavior from social norms, such as prostitution, drug abuse, and other activities that are morally and socially detrimental. Hotels are often viewed as potential spaces for such dissociative actions to occur. This study aims to analyze the business management system of Hotel Family Syariah 2 Yogyakarta and evaluate the strategies implemented to suppress the potential for deviant behavior in the hotel environment. This study uses a qualitative approach with a case study method. Data collection was carried out through observation, in-depth interviews with hotel management, and documentation. Data analysis was carried out descriptively qualitatively with an interactive approach using the Miles and Huberman model. The results of the study indicate that the application of sharia-based management principles has a significant role in creating a conducive, safe, and Islamic hotel environment. This strategy also contributes to building a positive image of the hotel in the community. One form of implementation of the sharia principles is the verification process for guests who stay, to ensure compliance with sharia provisions. In addition, the hotel also provides representative prayer facilities for Muslim guests as a form of support for their spiritual needs. The implementation of services based on sharia values ​​reflects management's commitment to creating a hotel environment that is not only comfortable, but also free from the potential for dissociative behavior.